1993
DOI: 10.1093/ajcn/57.2.161
|View full text |Cite
|
Sign up to set email alerts
|

An isotopic study of the effect of dietary carbohydrate on the metabolic fate of dietary leucine and phenylalanine

Abstract: The fate of dietary leucine and phenylalanine was studied in five healthy, young adult men, by using a dual, stable isotope-tracer infusion approach to estimate amino acid fluxes, splanchnic (Sp) uptake, and dietary of absorbed amino acid to the peripheral circulation. Subject received two, 4-h tracer infusions of [1-13C]leucine and [15N]phenylalanine infused through a feeding tube placed in the duodenum, and [5,5,5-2H3]leucine, [ring-2H5]phenylalanine, and [6,6-2H2]glucose infused simultaneously by vein. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 0 publications
4
11
0
1
Order By: Relevance
“…As far as whole splanchnic and peripheral anabolisms after a mixed soy protein meal are concerned, these results were found to be very consistent with those obtained using a previously developed model that had not been able to distinguish between the constitutive and exported parts of splanchnic proteins (27). In addition, and as shown in Table 5, model predictions for the regional metabolism of dietary N were validated in the light of findings available in the literature regarding the whole splanchnic (9,13,19,31,49,50) and peripheral (11,22,38,39,53,55) metabolism. In contrast, current knowledge concerning splanchnic interorgan metabolism and anabolism in the different splanchnic protein pools, which has mostly been obtained from experiments in animals (19,38,39,(48)(49)(50), remains unclear.…”
Section: Discussionsupporting
confidence: 83%
“…As far as whole splanchnic and peripheral anabolisms after a mixed soy protein meal are concerned, these results were found to be very consistent with those obtained using a previously developed model that had not been able to distinguish between the constitutive and exported parts of splanchnic proteins (27). In addition, and as shown in Table 5, model predictions for the regional metabolism of dietary N were validated in the light of findings available in the literature regarding the whole splanchnic (9,13,19,31,49,50) and peripheral (11,22,38,39,53,55) metabolism. In contrast, current knowledge concerning splanchnic interorgan metabolism and anabolism in the different splanchnic protein pools, which has mostly been obtained from experiments in animals (19,38,39,(48)(49)(50), remains unclear.…”
Section: Discussionsupporting
confidence: 83%
“…Other studies have provided indications of the important role of the splanchnic area in dietary nitrogen sparing by carbohydrates. Using an intraduodenal diet infusion, Krempf et al (14) reported that carbohydrates decreased the splanchnic uptake of dietary leucine and lowered whole-body leucine oxidation. This effect, which is not present for phenylalanine, may be dependent on the amino acid studied, particularly for amino acids that are taken up differently by the splanchnic area (34).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, through their action on gastric emptying, carbohydrates in a meal modify the gastrointestinal kinetics, which are thought to play a key role in the subsequent metabolic utilization of dietary nitrogen (10)(11)(12)(13). In addition, the presence of carbohydrates in a meal is thought to modulate the splanchnic metabolism and may thus also differently modify dietary and endogenous nitrogen utilization by the gut and liver and subsequent nitrogen utilization by peripheral tissues (5,14). The present study aimed to investigate the effects of sucrose on postprandial deamination of dietary and endogenous amino acids in humans, with particular emphasis on bioavailability factors.…”
Section: Introductionmentioning
confidence: 99%
“…Tout d'abord, même à moyen terme, l'utilisation métabolique d'un ensemble d'acides aminés réagit de manière complexe à la composition en acides aminés et à la quantité d'acides aminés [43,44]. Ainsi il est vraisemblable qu'à court terme, l'orientation immédiate des acides aminés dans les voies métaboliques puisse être optimale pour un profil en acides aminés différent de celui qui assure la couverture des besoins à long terme et que ce profil puisse dépendre de nombreux facteurs comme l'apport énergétique associé [34,[45][46][47]. En particulier, l'homme possède d'assez fortes capacités d'accommodation à des variations qualitatives aiguës de l'apport protéique [26,48].…”
Section: Utilisation Métabolique Des Acides Aminés Alimentairesunclassified